Measuring Stereotypes in Music: A Commentary on Susino and Schubert (2019) - Anglada-Tort, Manuel (Empirical Musicology Review, 2019)
In this commentary, I first discuss the strengths of the target paper and provide suggestions for future research. I proceed to point out an important limitation of the target study as well as contribute considerations relevant to measuring stereotypes in music. Finally, I present a novel theoretical account to explain music stereotyping, namely, the representativeness heuristic (Tversky & Kahneman, 1974), which I discuss within the broader framework of the behavioral economics of music.